Method of Teaching : GTM Versus CLT - Putri, Elda Selja (Modality Journal: International Journal of Linguistics and Literature, 2022)
One of the key components of implementing the goals of education in teaching and learning process, particularly in English classes is methodology. The primary goal of this article is to provide information regarding two remarkable procedures, GTM and CLT, as GTM was previously widely employed and CLT is currently very well known. This paper's strength is in its ability to increase educational professionals' understanding, particularly about English teaching methods. The principles used to compare the two approaches are clearly outlined. The principles are characteristics of the teaching-learning process, the nature of instruction, handling the students' feelings and emotions, the significance of the students' native languages, the language skills that are prioritized, and the teacher's response to the mistakes of the students. CLT is currently the more advantageous approach, while GTM still offers some advantages.Salah satu kunci dalam mengimplementasikan tujuan pendidikan dalam proses belajar mengajar, khususnya di kelas bahasa Inggris adalah metodologi. Tujuan utama dari artikel ini adalah untuk memberikan informasi mengenai dua metode yang luar biasa, GTM dan CLT, karena GTM sebelumnya banyak digunakan dan CLT saat ini sangat terkenal. Keunggulan tulisan ini terletak pada kemampuannya untuk meningkatkan pemahaman para profesional pendidik, khususnya tentang metode pengajaran bahasa Inggris. Prinsip-prinsip yang digunakan untuk membandingkan kedua metode tersebut diuraikan dengan jelas. Prinsip-prinsip tersebut adalah karakteristik proses belajar-mengajar, sifat pengajaran, penanganan perasaan dan emosi siswa, pentingnya bahasa ibu siswa, keterampilan bahasa yang diprioritaskan, dan respon guru terhadap kesalahan siswa. CLT saat ini merupakan pendekatan yang lebih menguntungkan, sementara GTM masih memiliki beberapa keuntungannya tersendiri.